LITERATURE IS THE FUTURE OF THE NATION - Bekmurodova Aziza Azamatovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
ABSTRACT In this article, the future of the literary nation lies in the realization of the identity of each nation in the expansion of the spiritual outlook and social development of one's mother tongue and the incomparable role of literature is stated.